2019
DOI: 10.1590/1983-80422019273338
|View full text |Cite
|
Sign up to set email alerts
|

Cuidadores formais e assistência paliativa sob a ótica da bioética

Abstract: Resumo A partir dos significados atribuídos ao tratamento paliativo por cuidadores formais de Pouso Alegre, Minas Gerais, Brasil, esta pesquisa pretende identificar e compreender possíveis hiatos na formação desses profissionais. O estudo é de caráter descritivo, exploratório e transversal; a amostragem foi intencional e seguiu a técnica bola de neve. Foram utilizados dois instrumentos para coletar os dados: questionário de caracterização pessoal e profissional e roteiro de entrevista semiestruturada. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Gender specificities can be observed with the predominance of females, a fact identified in several studies involving formal caregivers in Brazil [16][17][18] and in other countries 19,20 . Typically, care is essentially exercised by women, and even with advances in the world labor market, the perception that they are responsible for activities related to domestic work, including care, still persists 18 .…”
Section: Discussionmentioning
confidence: 92%
“…Gender specificities can be observed with the predominance of females, a fact identified in several studies involving formal caregivers in Brazil [16][17][18] and in other countries 19,20 . Typically, care is essentially exercised by women, and even with advances in the world labor market, the perception that they are responsible for activities related to domestic work, including care, still persists 18 .…”
Section: Discussionmentioning
confidence: 92%
“…These results are like other studies that found that the act of caring, even if assumed by a professional caregiver, involves an emotional burden when empathizing with the cared person. Such studies highlight the relevance of approaching care from the ethical principles of respect for autonomy, beneficence, and non-maleficence (28). New bioethical and philosophical approaches to the elderly's crucial social value in different societies are proposed from research and reflection.…”
Section: Discussionmentioning
confidence: 99%
“…"Cosmología" se utiliza en ocasiones como incluyendo, por ejemplo, "envenenamientos, una forma de brujería que tiene un lugar central en la cosmología" indígena (De Moura Pontes, Garnego & Rego, 2014). Otros artículos que utilizan el término "cosmología" haciendo alusión a lo indígena no lo definen, mas, puede suponerse que están haciendo alusión al mismo campo semántico que ocupa el término "cosmovisión" (Fortes Garcia Lorenzo, 2011;Da Silva, 2012;Camelo, 2017). En los casos en que cosmología no se evidencia ocupando el mismo campo semántico, cabría interpretar el término como el estudio de los astros (o de los dioses, en caso de considerar a los astros como dioses), como de hecho es utilizado hoy en día, pues la cosmología ha sido reconocida también como una antigua práctica indígena.…”
Section: Cosmovisiónunclassified